Apoptosis in Leukoaraiosis - Brown, William R.; Moody, Dixon M.; Thore, Clara R.; Challa, Venkata R. (American Journal of Neuroradiology, 2000)
Summary: We report a case of leukoaraiosis that was studied for apoptosis. In the neuropil, the number of cells that showed DNA fragmentation was 2.5 times as great in the area of leukoaraiosis as in the adjacent white matter (P = .004) and 25 times as great as in the nearby cortex (P < .001). Our findings suggest that apoptosis, predominantly of oligodendrocytes, is involved in the pathogenesis of leukoaraiosis. Within the area of leukoaraiosis, we also found numerous small veins that were partially occluded by severe collagenous thickening of the vessel walls. This collagenosis may have contributed to or resulted from chronic ischemia in that area.